MEDIA PLAYFULL CREATIVE ALPHABET BOARD SEBAGAI SARANA PEMBELAJARAN UNTUK MENSTIMULASI KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN - R, Setyaning Wiwik; Yafie, Evania; Astuti, Wuri (STKIP Pesisir Selatan, 2025)
Language is an important tool in building children's social skills and plays a role in all aspects of life, especially communication. The golden age is the development of language that requires stimulation through learning that is rich in fun language. The purpose of this research and development is to create a playful creative alphabet board